Changes in serum vitamin D and PTH values using denosumab with or without bisphosphonate pre-treatment in osteoporotic patients: a short-term study. Issue 1 (December 2015) - Nakamura, Yukio; Kamimura, Mikio; Ikegami, Shota; Mukaiyama, Keijiro; Uchiyama, Shigeharu; Taguchi, Akira; Kato, Hiroyuki
Abstract Background Denosumab is a fully human monoclonal antibody that inhibits receptor activator of nuclear factor kappa-β ligand (RANKL). Previous reports have shown that denosumab treatment of osteoporotic patients decreases bone resorption and fracture risk, but there have been no clinical studies on changes in bone turnover markers, 1, 25(OH)2 D3, or parathyroid hormone (PTH) in denosumab therapy with or without bisphosphonate (BP) pre-treatment in Japan. Methods Here, we report such findings in 22 patients (11 in the denosumab alone group and 11 in the BP pre-treated group) with osteoporosis following 4 months of treatment. Bone metabolism had been inhibited by prior BP administration in the BP pre-treated group. Results The bone resorption markers serum tartrate-resistant acid phosphatase type 5b and urinary type I collagen cross-linked N-telopeptide were significantly decreased from baseline values for the entire study period in both groups. The bone formation marker bone alkaline phosphatase was significantly decreased at 4 months in the denosumab alone group only, and N-terminal propeptide of type 1 procollagen was significantly decreased at 2 and 4 months in the denosumab alone group versus no remarkable change in the BP pre-treated group. In the denosumab alone group, 1, 25(OH)2 D3 and PTH were significantly increased at 1 week and decreased gradually thereafter, but these did not change notably in the BP pre-treated group. Conclusions Our results suggest that treatment with denosumab causes a strong inhibitory effect on bone resorption markers and mild inhibitory effect on bone formation markers. 1, 25(OH)2 D3 and PTH were significantly increased by denosumab but these did not change in the BP pre-treated group. Trial registration Current Controlled TrialsNCT02156960 . Registered 31 May 2014.